Artificial Intelligence Chatbot System For Student Inquiries In The LKC_FES Website - Siew, Yong Jun (2020)
The usual way of finding information on a university’s website is done by navigating through the website. It takes huge effort to find an answer to a user query as websites contains a vast amount of information. Statistics shows that LKCFES students find it hard to search for information on the website. It is a big learning curve for a user to use the website; such learning curve is an added disadvantage to new users when searching for information. Understanding the issues, this project utilizes the revolution of Artificial Intelligence to provide an easy solution at a much lower cost, one such technology that stands upon a huge wave of progress is Chatbot. The use of chatbot offers a new opportunity for an organization at providing personalized user experience at scale and encourages more interactions. Students are able to access information containing in LKCFES website with natural language eliminating the needs of traditional browsing. The implemented Chatbot System to support the LKCFES website had proven to help optimize students’ experience by encouraging more interaction between users and organization. Likewise, it also reduces the learning curves for new users in using the website.